ERBB1/2/3 Expression, Prognosis, and Immune Infiltration in Cutaneous Melanoma - Liu, Shougang; Geng, Rong; Lin, Eryi; Zhao, Peizhen; Chen, Yongfeng (Frontiers in Genetics, 2021)
Abstract 1 Background 2 The four ERBB tyrosine kinase family members [ERBB1 (epidermal growth factor receptor, EGFR), ERBB2 (HER2), ERBB3 (HER3), and ERBB4 (HER4)] (ERBB receptor family), previous studies have shown that they are related to the cutaneous melanoma. ERBB3 is the only member of the ERBBs that lacks tyrosine kinase activity, so it needs to dimer with other tyrosine kinase receptors to trigger the signaling pathway, while ERBB3 may dimer with all members of ERBB family. However, the relationship between the ERBBsand prognosis and immune infiltration in cutaneous melanoma are not completely clear. 3 Methods 4 The expression of the ERBBs wereanalyzed through Oncomine database, Gene Expression Profiling Interactive Analysis (GEPIA), respectively. Immunohistochemistry of ERBBs were obtained from the HPA database. ERBBs genes expression and mutation analysis in cutaneous melanoma from the cBioPortal. Functional annotation and KEGG pathway enrichment analysis from the Metascape. Correlations between ERBBs and 31 genes that neighboring and frequently altered were explored by GEPIA. Using the GEPIA database, we also investigated the relationship between ERBBs and myeloid derived suppressor cells (MDSC) in cutaneous melanoma. The progression-free survivaland different tumor stages of ERBBs were evaluated by GEPIA. The correlation of ERBBs to tumor-infiltrating immune cells and prognostic（5-year survival rate） was tested by Tumor Immune Estimation Resource (TIMER). 5 Results 6 The expression levels of ERBB1/2 in cutaneous melanoma were lower than that in normal skin tissues in at least two databases; on the contrary, the expression level of ERBB3 in cutaneous melanoma was higher in at two databases. Low expression levels of ERBB1and ERBB2, High expression level of ERBB3 were positively correlated with the 5-year survival rate of cutaneous melanoma patients . The expression of ERBB4 was not correlated with prognosis. ERBBs were not associated with tumor stage and progression-free survival in melanoma patients. 7 Conclusion This study provides a preliminary exploration of the prognosis and immunity of the ERBBs family in cutaneous melanoma. These results suggest that ERBB1/2/3 can be considered as an early prognostic marker for cutaneous melanoma and a potential therapeutic target.